FACTORS ASSOCIATED WITH LEFT VENTRICULAR LONGITUDINAL STRAIN INDICES IN PATIENTS WITH MITRAL STENOSIS (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate factors associated with left ventricular global longitudinal strain (GLS) assessed by speckle-tracking echocardiography in patients with mitral stenosis.Methods: This was a descriptive analytical study conducted in patients with mitral stenosis. GLS was assessed using speckle-tracking echocardiography (STE), and its associations with left ventricular function, right ventricular function, and hemodynamic parameters were analyzed.Results: Mean GLS (GLS-avg) showed a moderate inverse correlation with biplane ejection fraction (EF) that was statistically significant (r = -0.378; p = 0.039), but was not associated with fractional shortening (FS). GLS-avg also demonstrated a moderate inverse and statistically significant correlation with tricuspid annular systolic velocity s′ (r = -0.455; p = 0.012). The correlation between GLS-avg and TAPSE was moderate but did not reach statistical significance (r = -0.328; p = 0.077), whereas the correlation with FAC was negligible (r = -0.106; p = 0.578). No significant associations were found between GLS and left atrial volume or systolic pulmonary artery pressure.Conclusion: In patients with mitral stenosis, GLS was associated with biplane EF and, in particular, with tricuspid annular systolic velocity s′. Among the parameters examined, tricuspid annular s′ most clearly reflected the functional interaction between the left and right ventricles.
Keywords: mitral stenosis, speckle tracking echocardiography, cardiovascular risks.